Vulnerability and minorities: Analysis of the incidence of notifications of violence against people with disabilities and the legal contribution in the process of social inclusion (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
People with disabilities (PWDs) are a minority group and are often exposed to situations of violence and vulnerability. This research aimed to analyze the permanent violence against these individuals through a historical and statistical analysis. The present article presents applied research with a qualitative approach, descriptive objectives, and a bibliographic and document-based review. After the study, it is clear that violence, in general, constitutes a complex subject due to the different factors to which it is related. In Brazil, this phenomenon derives from a colonial heritage and violence is linked to the concepts of minority and vulnerability in the country's current scenario. As analyzed in this study, people with disabilities, considered part of a social minority, have suffered exclusion and oppression throughout human history. Based on statistical data about the current situation of violence, in which these people are inserted, it was found that there is a higher rate of violence against those who have intellectual disabilities, and domestic violence is the most common type. Regarding the nature of violence, physical violence is the one with the highest number of notifications, and sexual violence prominent in children, adolescents, and adults. The conclusion is that, despite the legal advances related to the structuring of laws that ensure the human rights and dignity of people with disabilities, the present scenario of violence corroborates the situation of vulnerability of this minority.